From Comprehension to Production Insights from an Integrated Reading–Writing Assessment in Junior High School in Indonesia - Rizky Nugraha; Fazri Nur Yusuf (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2026)
AbstractAssessment is one language teaching aspect which measures and calculates learning outcomes and learning process through teacher’s feedback. In English as a Foreign Language (EFL) settings, where learners develop integrated skills, formative assessment is especially valuable: it can reveal not only what learners know, but also how they develop integrated competencies across reading and writing. However, many teachers still rely on discrete, product-focused tests that separate receptive and productive skills rather than integrating them. This study therefore investigates an integrated formative assessment implemented with grade VII English learners in an Indonesian junior high school and both students’ and the teacher’s responses to the assessment’s clarity, relevance, and feedback mechanisms. The study found that most students were able to comprehend descriptive texts, as indicated by the mean score of 6.87 and the fact that 55.74% of the students scored above the average. However, the writing assessment revealed notable challenges, particularly in vocabulary mastery and the use of pronouns and conjunctions. Although students were able to generate ideas, their written production was often limited by insufficient vocabulary knowledge and reliance on memorized expressions. Overall, the integrated reading–writing assessment provides meaningful information about students’ language proficiency and learning progress. With strengthened instructional support, particularly in vocabulary and writing mechanics, this assessment approach is suitable for continued use in Grade VII English instruction.